Using Recombinant Human Collagen With Basic Fibroblast Growth Factor to Provide a Simulated Extracellular Matrix Microenvironment for the Revascularization and Attachment of Islets to the Transplantation Region - Zhu, Qunyan; Lu, Cuitao; Jiang, Xuan; Yao, Qing; Jiang, Xue; Huang, Zhiwei; Jiang, Yina; Peng, Lei; Fu, Hongxing; Zhao, Yingzheng (Frontiers in Pharmacology, 2020)
Islet transplantation is considered a potential therapeutic option to reverse diabetes. The pancreatic basement membrane contains a variety of extracellular matrix proteins. The abundant extracellular matrix is essential for the survival of transplanted islets. However, the extracellular matrix proteins necessary for maintaining islet vascularization and innervation are impaired by enzymatic digestion in the isolation process before islet transplantation, leading to destruction of islet microvessels. These are the primary concern and major barrier for long-term islet survival and function. Thus, it is crucial to create a appropriate microenvironment for improving revascularization and islet function to achieve better transplantation outcome. Given the importance of the presence of extracellular matrix proteins for islets, we introduce recombinant human collagen (RHC) to construct a simulated extracellular matrix (ECM) microenvironment. To accelerate revascularization and reduce islet injury, we add bFGF to RHC, a growth factor that has been shown to promote angiogenesis. In order to verify the outcome, islets were treated with RHC combination containing bFGF and then implant into kidney capsule in type 1 diabetic mice models. After transplantation, 30 day-long monitoring displayed that 16 mg-60 ng RHC-bFGF group could serve as superior transplantation outcome. It reversed the hyperglycemia condition in host rapidly and the OGTT showed a similar pattern with the control group. Histological assessment showed that 16 mg-60 ng RHC-bFGF group attenuated apoptosis, promoted cellular proliferation, triggered vascularization and inhibited inflammation reaction. In summary, this work demonstrates that application of 16 mg-60 ng RHC-bFGF and islets composite enhance the islet survival, function and long-term transplantation efficiency.